Early superior mesenteric artery revascularization for acute type A aortic dissection with cardiac tamponade and mesenteric malperfusion. Issue 12 (9th September 2020) - Kusadokoro, Sho; Kimura, Naoyuki; Miyoshi, Kosuke; Hori, Daijiro; Shiraishi, Manabu; Yamaguchi, Atsushi
Abstract: We report herein the successful treatment of a case of acute type A aortic dissection complicated by cardiac tamponade and mesenteric malperfusion. The patient was a 60‐year‐old man with back and abdominal pain and in shock, who was transported to our hospital 2 h after symptom onset. Computed tomography revealed DeBakey type I dissection with massive hemopericardium and obstruction of both the celiac artery and superior mesenteric artery. After emergency pericardiotomy and removal of the hematoma, superior mesenteric artery‐external iliac artery bypass was constructed with a vein graft, and this restored mesenteric perfusion. Open distal hemiarch replacement was then performed. The postoperative course was uneventful. Superior mesenteric artery revascularization achieved immediately after release of the cardiac tamponade prevented further mesenteric ischemia and paved the way for the aortic repair.